Influence of age and fitness level on immune responses of T and NK cells in healthy physically active subjects after strenuous aerobic exercise: a cross-sectional study - Almeida-Neto, Paulo Francisco de; Gonçalves, Ciro Alexandre Mercês; Wilde, Phelipe; Jaggers, Jason R.; Júnior, Geraldo Barroso Cavalcanti; de Farias Sales, Valéria Soraya; Medeiros, Radamés Maciel Vitor; Dantas, Paulo Moreira Silva; Cabral, Breno Guilherme de Araújo Tinôco (Frontiers in Immunology, 2023)
The aim of this study is to analyze whether immune responses after strenuous exercise are influenced by chronological age and fitness level in physically active healthy men. Cross-sectional study with a sample of 32 physically active men. Participants were divided into two groups based on chronological age (younger: age 21.8±1.8 vs. older: age 34.6±8.3) and subsequently regrouped and divided based on fitness level (More conditioned: excellent and superior VO2max vs. Less conditioned: VO2max: weak, regular and good).Fitness was classified according to VO2max levels obtained by a treadmill test using a gas analyzer. Before and immediately after the ergospirometry test, blood samples were collected for evaluation of immunological markers: leukocytes, neutrophils, lymphocytes and subpopulations. Chronological age had a moderate effect on CD3+CD4+ lymphocyte count (effect size: 0.204) and CD4/CD8 ratio (effect size: 0.278), favoring older subjects. The level of physical fitness had no significant effect on the analyzed immunological markers.Immune responses observed immediately after strenuous exercise may be more dependent on chronological age than on fitness level in healthy, physically active men.